Comparison of lumbar segmental stabilization and general exercises on clinical and radiologic criteria in grade‐I spondylolisthesis patients: A double‐blind randomized controlled trial. (28th April 2020) - Mohammadimajd, Elaheh; Lotfinia, Iraj; Salahzadeh, Zahra; Aghazadeh, Nasser; Noras, Parisa; Ghaderi, Fariba; Poureisa, Masoud; Sarbakhsh, Parvin; Choopani, Rasool
Abstract: Objectives: The effects of different physiotherapy protocols on patients suffering from grade‐I spondylolisthesis have been thus far examined in a limited number of clinical trials. Therefore, the main purpose of this study was to compare the effects of lumbar segmental stabilization and general exercises on clinical and radiologic criteria in grade‐I spondylolisthesis patients. Methods: This study was a double‐blind randomized controlled trial (RCT) with a test–retest design and parallel groups. A total of 26 patients with grade‐I spondylolisthesis were thus randomly assigned to experimental group (13 patients, lumbar segmental stabilization exercises) and control group (13 patients, general exercises). Subsequently, pain, functional disability, kinesiophobia, translational motion, angular motion and slip percentage of the vertebra were investigated. Results: Of the 120 people recruited in this study, only 26 patients were eligible. According to pre/post‐intervention comparison, a statistically significant decrease was observed in the experimental group in terms of pain ( p = 0.000), functional disability ( p = 0.004), kinesiophobia ( p = 0.002), translational motion ( p = 0.043) and angular motion ( p = 0.011), but not for slip percentage ( p = 0.122). Considering the control group, a statistically significant decline was reported for pain ( p = 0.043) and functional disability ( p = 0.002). However, no significant differences were found for other variables in the control group. With regard to inter‐group comparison, there was no statistically significant difference between the two groups regarding the given variables except for kinesiophobia ( p = 0.040). Conclusion: Both lumbar segmental stabilization and general exercises led to reduction in pain and functional disability of patients with grade‐I spondylolisthesis. Therefore, lumbar segmental stabilization exercises seemed to be better than general ones with reference to improving kinesiophobia and intervertebral movements.